Degradable film mulching recruited beneficial microbiota and increased rhizosphere bacterial diversity in sunflower - Tiantian Meng; Hengtong Bu; Xiangqian Zhang; Xuanyi Chen; Weini Wang; Min Zhao; Junmei Liu; Jianwei Zhang; Dejian Zhang; Zhanyuan Lu; Xiaoyu Zhao (Scientific Reports)
Abstract The degradable film can solve the problem that the traditional plastic film is difficult to recycle and heavy pollution for a long time. The effects of degraded film mulching on microbial diversity are significant. However, the responses of relevant microbial communities to degraded film mulching in different ecological niches (e.g., bulk soil, rhizosphere and endosphere) of sunflower roots are poorly understood. This study analyzed the effects of plastics film mulching on bacterial and fungal α-diversities (Shannon index), community assembly process, key dominant species of sunflower different ecological niches in roots. The results showed that degradable film mulching significantly increased the α-diversity (Shannon index) of bulk soil and rhizosphere soil bacteria and decreased the α-diversity of fungi (Shannon index), and the mulching treatment promoted the gradual shift of the rhizosphere microbial community assembly process to a deterministic process. Degradation film mulching increased the connectivity and complexity of bacterial networks and decreased the complexity of fungal networks. Plastic film mulching improves soil nutrients, temperature and moisture, enhances the positive correlation among microorganisms. At the same time, core species such as Amycolatopsis, Rhizobiaceae, and Sphingomonas that recruit beneficial microorganisms and accelerate the degradation of plastic film are significantly enriched. Degradable film covering promoted soil nutrient cycling, increased urease, alkaline phosphatase, sucrase, and thus increased sunflower yield. A comprehensive analysis of random forest and structural equations showed that the main driving microbial factors of yield were bulk soil bacterial diversity and endosphere fungal diversity. This study provides new ideas for the analysis of soil microbial mutual feedback mechanisms between degraded film mulch and rhizosphere ecosystems.